The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3py01086d
|View full text |Cite
|
Sign up to set email alerts
|

Melt memory in propene–pentene isotactic copolymers: the case of defects hosted in the crystals

Fabio De Stefano,
Alessandra Cicolella,
Annachiara Barreca
et al.

Abstract: Incorporation of pentene in isotactic polypropylene produces a memory of the crystalline state in the melt that persists up to temperatures higher than the melting temperature giving self-nucleation and favoring crystallization of the γ form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Furthermore, within the processing melt temperature range of 292-323 • C, the SN behavior of PPS remains unchanged with temperature variations [26]. A similar melt memory effect is observed in many copolymers [27][28][29][30][31][32] and some homopolymers [33][34][35][36][37][38]. They all demonstrate SN behaviors a few to several tens of degrees above their melting point.…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, within the processing melt temperature range of 292-323 • C, the SN behavior of PPS remains unchanged with temperature variations [26]. A similar melt memory effect is observed in many copolymers [27][28][29][30][31][32] and some homopolymers [33][34][35][36][37][38]. They all demonstrate SN behaviors a few to several tens of degrees above their melting point.…”
Section: Introductionmentioning
confidence: 53%
“…Similar observations were reported by De Rosa et al in the a-phase of propylene-pentene isotactic copolymers, which were ascribed to the inclusion of pentene co-units in acrystal. 21,[52][53][54] However, a common feature in ethylene-1-alkene copolymers is that co-units larger than methyl are excluded from the crystal lattice. Therefore, the expansion in the unit cell dimensions of the orthorhombic phase can be interpreted by a strain effect caused by congregation of co-units at the interphase of crystallites.…”
Section: Crystalline Structure Of Ethylene-1-alkene Copolymersmentioning
confidence: 99%
“…18,33 They both attributed this effect to a shifting-up of the local melting point, which was proposed to be the complex topology of the amorphous phase generated during the crystallization of constitutionally inhomogeneous polymer chains with relatively long ethylene sequences. In addition, De Rosa et al reported a remarkable melt memory in propene–pentene isotactic copolymers 21 and stereodefective iPP. 35 Their results indicated that the melt memory effect of iPP, which persists in the melt up to high temperatures, is evident not only in copolymers with non-crystallizable comonomers, but also in those with small defects largely included in the crystals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations